Evaluación de la cosecha de plantas seleccionadas de henequén (Agave fourcroydes Lem) y propagadas in vitro - Gerardo González; Silvia Alemán; Hilter Figueroa Saavedra; Arisdorgan Diéguez; Ramiro Herrera (European Scientific Journal, ESJ, 2018)
This paper focuses on the establishment of a system of in vitro cloning of henequen, of which the behavior of these plants in production conditions is unknown. With the objective of evaluating the agricultural yields in selected henequen and plants propagated in vitro, five harvests were carried out during the years 2005 to 2009. In the five harvest, the yields in fiber (tn/ha) were higher in the vitroplantas in regards to conventionally propagated plants. The first harvest was done three years after the plantation was carried out. In all crops, line 4 statistically surpassed lines 1 and 9 in terms of the fibre content, which showed a greater productive potential. The histological characterization of these plants showed a greater number of vascular bundle and strands of fibers in the vitroplants with regard to plants multiplied by the conventional method. This, however, showed a significant correlation with more fibre content in the first.